Abdominal ultrasound cervical length measurement in normal pregnant women between 20-23 weeks - Huamán G., Moisés (2014)
Objectives: To assess the feasibility of measuring cervical by transabdominal ultrasound between 20 and 23 weeks of gestation and compare these measurements with those obtained by transvaginal ultrasound. Design: Cross-sectional study. Setting: Instituto Latinoamericano de Salud Reproductiva (ILSAR), Lima, Peru. Participants: Normal pregnant women with no risk factors for preterm delivery (PTD). Methods: Cervical length was measured to 67 normal pregnant women 20-23 weeks by transabdominal ultrasound. In 30 women cervical length was measured by abdominal ultrasound using 3-5 MHZ convex transducer and by vaginal ultrasound with 5-7 MHZ endotransducer. Main outcome measures: Cervical length measurement. Results: The cervix was satisfactorily measured by transabdominal ultrasound in 65 women (97%). There was good correlation between transabdominal and transvaginal measurement (r<.0.646, p<0.001) with no significant difference between those measurements (p:0.126). Conclusions: The cervix could be measured by transabdominal ultrasound in 97% of women. There was correlation between transabdominal and transvaginal ultrasound measurements.